Understanding Level Of Licensed Referees In Pelalawan District Of Football Game Rules: Tingkat Pemahaman Wasit Berlisensi Di Kabupaten Pelalawan Terhadap Peraturan Permainan Sepakbola - Muhammad Chusnul Badri; Merlina Sari (Jurnal Olahraga dan Kesehatan (ORKES), 2023)
This research aims to determine the level of understanding of licensed referees in Pelalawan district regarding the rules of the football game. This research is quantitative descriptive. The research method used is a survey and data collection techniques using questionnaires.The subjects of this research were 25 licensed referees. The research results show that the level of understanding of licensed referees in Pelalawan Regency regarding the rules of the football game is in the Very High category. This is shown in the number of respondents who answered most in the very high category, namely 3 referees (12%). Then the number of referees who answered in the medium category was 0 referees (0%). Furthermore, the number of referees who answered in the high category was 22 referees (88%). Meanwhile, the number of referees who answered in the very low category was 0 referees (0%) and there were no referees (0.00%) who answered in the low category.